PALESTINIAN SOLIDARITY AND THE DYNAMICS OF BOYCOTT MOVEMENTS: A SOCIAL IDENTITY THEORY PERSPECTIVE - Siti Norayu Mohd Basir; Nor Hafizan Habib Sultan; Mohd Arsad Johanis; Siti Balkis Mohamed Ibrahim (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
The Israel-Palestine conflict is a longstanding issue, deeply rooted in decades of history, religion, politics, and resource disputes. This conflict has resulted in numerous military confrontations, with over 35,000 Palestinians losing their lives since October 7, 2023. Despite peace efforts such as the Oslo Accords, achieving lasting peace requires a significant political commitment. In response, Palestinian solidarity movements—through protests, humanitarian aid, and economic boycotts targeting Israel—seek justice and the restoration of land rights. This study examines boycotting Israeli-related products and services as a global solidarity action in opposition to Israel’s war crimes and oppression of Palestinians. Drawing on Social Identity Theory (SIT) by Henri Tajfel and John Turner, it illustrates how individual identities are shaped not only by personal traits but also by belonging to social groups with shared values and objectives. The boycott fosters a collective identity committed to justice. Furthermore, social media amplifies global awareness, mobilizing individuals and organizations to apply economic pressure on Israel to end its Zionist atrocities